PERBEDAAN KEPUASAN KERJA DITINJAU DARI LOCUS OF CONTROL PADA KARYAWAN DI BPR KEMBANG PARAMA MAGELANG - Maharani, Keba Dinta; Soetjiningsih, Christiana Hari (Jurnal Psikologi : Media Ilmiah Psikologi, 2019)
The aim of this research is to find differences of job satisfaction on employees in terms of internal locus of control and external locus of control. This study was performed on 60 employees at BPR Kembang Parama Magelang. The author uses the comparative method of two samples. In addition, the author uses t test as a method of data analysis. The measurement of job satisfaction uses nine aspects, named pay, promotion, supervisor, additional allowance, achievement, procedure and operating procedure, collegeus, job description, and communication. While the measurement of locus of control use three aspects, named internality, powerful others, and chance. This study states that there are not differences in job satisfaction on employees who have an orientation at internal locus of control with employees who have an orientation at external locus of control with a significance value of = 0,739 so that the hypothesis in this study is rejected. Keywords : Job Satisfaction, Locus of Control, Employees